Hemophilia Gene Therapy: New Development from Bench to Bed Side - Guo, Xiao-Lu; Chung, Tsai-Hua; Qin, Yue; Zheng, Jie; Zheng, Huyong; Sheng, Liyuan; Wynn, Tung; Chang, Lung-Ji (Current Gene Therapy, 2019)
Novel gene therapy strategies have changed the prognosis of many inherited diseases in recent years. New development in genetic tools and study models has brought us closer to a complete cure for hemophilia. This review will address the latest gene therapy research in hemophilia A and B including gene therapy tools, genetic strategies and animal models. It also summarizes the results of recent clinical trials. Potential solutions are discussed regarding the current barriers in gene therapy for hemophilia.
Keywords: Gene therapy